Raging in service of the self: exploring a five-year old boy's aggression within his play therapy - Smith, Austin (Rhodes University, Faculty of Humanities, Department of Psychology, 2006)
This thesis takes the form of an in-depth case study within which the play therapy process of an aggressive 5-year-old boy was explored. The aim of the research was to examine the abundant expressions of aggression that were present within his therapy, and in so doing reflect their rich communicative content and their relevance and purpose in the development of his Self. Object relations theory formed the lens and theoretical context for this research with Winnicott's contributions and Parens' model of aggression being considered in particular. A detailed data resource of the therapy process was compiled and transposed into narrative form. These narratives were reviewed with a reading guide as a means to facilitate a hermeneutic exploration of the data. The emergent themes were considered against the case data and the current theory, which allowed for their further analysis and development. From this the value of using Parens' model was considered and deemed useful although limited in its contribution. The analysis and the themes which emerged conveyed how within this case the child's aggression presented as: a significant feature of his ambivalence towards relationships; a powerful and pervasive protective fantasy of omnipotence; inherently linked to his sense of self and self expression; and as actively involved in his True Self's hope-filled attempts for an alternative experience. This thesis provides a descriptive account of a challenging case, offering insights into the value and meaningful content of aggressive behaviours, with the intention being to reflect that which is often not easily appreciated or readily observable within such a therapy process, a trace of hope.
Keywords: Play therapy; Aggressiveness in children; Self-perception in children; Child development; Child psychology